MENGANALISIS KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS XI MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Nur Fitri Aisyah; Kurratul ‘Aini; Syarifah Syarifah; Anggun Wicaksono; Yustina Hapida; Ummi Hiras Habisukan; Amin Nurokhman; Weni Lestari; Rian Oktiansyah; Fahmy Armanda (Bioilmi: Jurnal Pendidikan, 2022)
PBL is a teaching method that can help students understand the subject matter and improve their problem-solving abilities. The purpose of this study is to see how the problem-based learning (PBL) model affects students' problem-solving abilities with reproductive system material. This is a pre-experimental study with a one-group pretest-posttest design. Non-probability sampling is used, along with total sampling. The research sample consisted of 39 students from Class XI. The data collection technique used pretest and posttest instruments, and the data analysis technique used was the One-Sample KS Test, with an average pretest result of 23.08 with a significance of 0.00, a posttest average of 85.18 with a significance of 0.03, and an average N-Gain of 0.81 with a significance of 0.01 as evidenced by statistical analysis, which states that the data significance is 0.05, indicating that Problem Based Learning has an effect.